Implementation of Talent Management as A Strategy for Enhancing the Professionalism of Civil Servants - Aghnia Nurhabibah; Sri Wulandari (Journal of World Science, 2026)
Bureaucratic reform requires professional and adaptive management of the state civil apparatus (ASN). One of the strategic instruments developed by the government is talent management to ensure the placement of employees according to potential, competence, and performance. This study aims to analyze the implementation of talent management at the Cirebon Regency Personnel and Human Resources Development Agency (BKPSDM), identify obstacles to its implementation, and examine efforts made to improve the professionalism of ASN. The theoretical framework of the research refers to the concept of talent management (Collings & Mellahi; Armstrong & Taylor), the Gallardo-Gallardo dimension of talent (natural ability, mastery, commitment, fit), as well as the subject's approach. The research method used is qualitative with a descriptive approach. Data were collected through in-depth interviews, observations, and documentation studies of purposively selected key informants and supporters. The results of the study show that talent management in the Cirebon Regency BKPSDM has been implemented in stages through competency and potential assessments, ASN profile mapping, and the implementation of a nine-box matrix. However, its implementation has not been optimal due to the limitations of assessors, political intervention, low digital literacy, and a work culture that is not yet performance-oriented. Improvement efforts are carried out through strengthening socialization, consistency in the implementation of the merit system, infrastructure development, and changes in work culture. It was concluded that talent management has the potential to significantly improve the professionalism of ASN, but it requires leadership commitment and sustainable institutional strengthening.